Optimasi suhu dan waktu pengeringan pada kegiatan pascapanen jagung (Zea Mays L) - Titik Ismandari (Teknologi Pangan: Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2023)
𝘊𝘰𝘳𝘯 𝘪𝘴 𝘰𝘯𝘦 𝘰𝘧 𝘵𝘩𝘦 𝘴𝘶𝘱𝘦𝘳𝘪𝘰𝘳 𝘢𝘨𝘳𝘪𝘤𝘶𝘭𝘵𝘶𝘳𝘢𝘭 𝘱𝘳𝘰𝘥𝘶𝘤𝘵𝘴 𝘪𝘯 𝘵𝘩𝘦 𝘱𝘳𝘰𝘷𝘪𝘯𝘤𝘦 𝘰𝘧 𝘕𝘰𝘳𝘵𝘩 𝘒𝘢𝘭𝘪𝘮𝘢𝘯𝘵𝘢𝘯, 𝘦𝘷𝘦𝘯 𝘪𝘵𝘴 𝘱𝘳𝘰𝘥𝘶𝘤𝘵𝘪𝘰𝘯 𝘪𝘴 𝘦𝘹𝘱𝘦𝘤𝘵𝘦𝘥 𝘵𝘰 𝘣𝘦 𝘢𝘣𝘭𝘦 𝘵𝘰 𝘴𝘶𝘱𝘱𝘰𝘳𝘵 𝘵𝘩𝘦 𝘧𝘶𝘭𝘧𝘪𝘭𝘭𝘮𝘦𝘯𝘵 𝘰𝘧 𝘯𝘢𝘵𝘪𝘰𝘯𝘢𝘭 𝘮𝘢𝘪𝘻𝘦 𝘯𝘦𝘦𝘥𝘴. 𝘏𝘰𝘸𝘦𝘷𝘦𝘳, 𝘪𝘯 𝘳𝘦𝘤𝘦𝘯𝘵 𝘺𝘦𝘢𝘳𝘴 𝘤𝘰𝘳𝘯 𝘱𝘳𝘰𝘥𝘶𝘤𝘵𝘪𝘰𝘯 𝘪𝘯 𝘒𝘢𝘭𝘵𝘢𝘳𝘢 𝘩𝘢𝘴 𝘥𝘦𝘤𝘳𝘦𝘢𝘴𝘦𝘥 𝘥𝘶𝘦 𝘵𝘰 𝘪𝘮𝘱𝘳𝘰𝘱𝘦𝘳 𝘱𝘰𝘴𝘵-𝘩𝘢𝘳𝘷𝘦𝘴𝘵 𝘩𝘢𝘯𝘥𝘭𝘪𝘯𝘨. 𝘛𝘩𝘦 𝘱𝘰𝘴𝘵-𝘩𝘢𝘳𝘷𝘦𝘴𝘵 𝘩𝘢𝘯𝘥𝘭𝘪𝘯𝘨 𝘮𝘦𝘵𝘩𝘰𝘥 𝘥𝘦𝘵𝘦𝘳𝘮𝘪𝘯𝘦𝘴 𝘵𝘩𝘦 𝘥𝘦𝘨𝘳𝘦𝘦 𝘰𝘧 𝘢𝘤𝘩𝘪𝘦𝘷𝘦𝘮𝘦𝘯𝘵 𝘰𝘧 𝘲𝘶𝘢𝘭𝘪𝘵𝘺 𝘪𝘮𝘱𝘳𝘰𝘷𝘦𝘮𝘦𝘯𝘵, 𝘴𝘶𝘱𝘱𝘳𝘦𝘴𝘴𝘦𝘴 𝘵𝘩𝘦 𝘭𝘦𝘷𝘦𝘭 𝘰𝘧 𝘲𝘶𝘢𝘯𝘵𝘪𝘵𝘢𝘵𝘪𝘷𝘦 𝘢𝘯𝘥 𝘲𝘶𝘢𝘭𝘪𝘵𝘢𝘵𝘪𝘷𝘦 𝘭𝘰𝘴𝘴𝘦𝘴. 𝘛𝘩𝘦 𝘴𝘭𝘰𝘸 𝘥𝘳𝘺𝘪𝘯𝘨 𝘱𝘳𝘰𝘤𝘦𝘴𝘴 𝘤𝘢𝘯 𝘳𝘦𝘥𝘶𝘤𝘦 𝘵𝘩𝘦 𝘷𝘪𝘢𝘣𝘪𝘭𝘪𝘵𝘺 𝘰𝘧 𝘤𝘰𝘳𝘯 𝘴𝘦𝘦𝘥𝘴. 𝘛𝘩𝘪𝘴 𝘴𝘵𝘶𝘥𝘺 𝘢𝘪𝘮𝘴 𝘵𝘰 𝘥𝘦𝘵𝘦𝘳𝘮𝘪𝘯𝘦 𝘵𝘩𝘦 𝘰𝘱𝘵𝘪𝘮𝘪𝘻𝘢𝘵𝘪𝘰𝘯 𝘰𝘧 𝘥𝘳𝘺𝘪𝘯𝘨 𝘵𝘪𝘮𝘦 𝘢𝘯𝘥 𝘵𝘦𝘮𝘱𝘦𝘳𝘢𝘵𝘶𝘳𝘦 𝘰𝘧 𝘤𝘰𝘳𝘯 𝘴𝘦𝘦𝘥𝘴 𝘸𝘩𝘪𝘤𝘩 𝘢𝘳𝘦 𝘥𝘳𝘪𝘦𝘥 𝘶𝘴𝘪𝘯𝘨 𝘢 𝘵𝘳𝘢𝘺 𝘥𝘳𝘺𝘦𝘳.𝘛𝘩𝘪𝘴 𝘦𝘹𝘱𝘦𝘳𝘪𝘮𝘦𝘯𝘵 𝘶𝘴𝘦𝘴 𝘢 𝘤𝘦𝘯𝘵𝘳𝘢𝘭 𝘤𝘰𝘮𝘱𝘰𝘴𝘪𝘵𝘦 𝘥𝘦𝘴𝘪𝘨𝘯 (𝘊𝘦𝘯𝘵𝘳𝘢𝘭 𝘊𝘰𝘮𝘱𝘰𝘴𝘪𝘵𝘦 𝘋𝘦𝘴𝘪𝘨𝘯). 𝘛𝘩𝘦 𝘥𝘳𝘺𝘪𝘯𝘨 𝘱𝘳𝘰𝘤𝘦𝘴𝘴 𝘶𝘴𝘦𝘴 𝘵𝘩𝘦 𝘙𝘦𝘴𝘱𝘰𝘯𝘴𝘦 𝘚𝘶𝘳𝘧𝘢𝘤𝘦 𝘔𝘦𝘵𝘩𝘰𝘥/𝘙𝘚𝘔 𝘈𝘯𝘢𝘭𝘺𝘴𝘪𝘴, 𝘸𝘪𝘵𝘩 𝘳𝘦𝘴𝘱𝘰𝘯𝘴𝘦 𝘷𝘢𝘳𝘪𝘢𝘣𝘭𝘦𝘴 (𝘠): 𝘮𝘰𝘪𝘴𝘵𝘶𝘳𝘦 𝘤𝘰𝘯𝘵𝘦𝘯𝘵, 𝘷𝘪𝘨𝘰𝘳 𝘪𝘯𝘥𝘦𝘹, 𝘨𝘳𝘰𝘸𝘵𝘩 𝘴𝘱𝘦𝘦𝘥, 𝘨𝘦𝘳𝘮𝘪𝘯𝘢𝘵𝘪𝘰𝘯 𝘤𝘢𝘱𝘢𝘤𝘪𝘵𝘺, 𝘢𝘯𝘥 𝘨𝘳𝘰𝘸𝘵𝘩 𝘱𝘰𝘵𝘦𝘯𝘵𝘪𝘢𝘭. 𝘞𝘩𝘪𝘭𝘦 𝘵𝘩𝘦 𝘪𝘯𝘥𝘦𝘱𝘦𝘯𝘥𝘦𝘯𝘵 𝘷𝘢𝘳𝘪𝘢𝘣𝘭𝘦 (𝘟) 𝘤𝘰𝘯𝘴𝘪𝘴𝘵𝘴 𝘰𝘧 2 𝘧𝘢𝘤𝘵𝘰𝘳𝘴, 𝘯𝘢𝘮𝘦𝘭𝘺 𝘥𝘳𝘺𝘪𝘯𝘨 𝘵𝘦𝘮𝘱𝘦𝘳𝘢𝘵𝘶𝘳𝘦 (𝘟1) 𝘢𝘯𝘥 𝘥𝘳𝘺𝘪𝘯𝘨 𝘵𝘪𝘮𝘦 (𝘟2). 𝘛𝘩𝘦 𝘳𝘦𝘴𝘶𝘭𝘵𝘴 𝘴𝘩𝘰𝘸𝘦𝘥 𝘵𝘩𝘢𝘵 𝘵𝘩𝘦 𝘰𝘱𝘵𝘪𝘮𝘪𝘻𝘢𝘵𝘪𝘰𝘯 𝘰𝘧 𝘥𝘳𝘺𝘪𝘯𝘨 𝘵𝘪𝘮𝘦 𝘢𝘯𝘥 𝘵𝘦𝘮𝘱𝘦𝘳𝘢𝘵𝘶𝘳𝘦 𝘸𝘢𝘴 𝘢𝘵 52.62 º𝘊 𝘸𝘪𝘵𝘩 𝘢 𝘥𝘳𝘺𝘪𝘯𝘨 𝘵𝘪𝘮𝘦 𝘰𝘧 24.14 𝘩𝘰𝘶𝘳𝘴. 𝘛𝘩𝘦 𝘸𝘢𝘵𝘦𝘳 𝘤𝘰𝘯𝘵𝘦𝘯𝘵 𝘱𝘳𝘰𝘥𝘶𝘤𝘦𝘥 𝘸𝘢𝘴 12.82%, 𝘵𝘩𝘦 𝘨𝘳𝘰𝘸𝘵𝘩 𝘱𝘰𝘵𝘦𝘯𝘵𝘪𝘢𝘭 𝘸𝘢𝘴 72.04%, 𝘵𝘩𝘦 𝘨𝘦𝘳𝘮𝘪𝘯𝘢𝘵𝘪𝘰𝘯 𝘳𝘢𝘵𝘦 𝘸𝘢𝘴 70.39%, 𝘵𝘩𝘦 𝘨𝘳𝘰𝘸𝘵𝘩 𝘳𝘢𝘵𝘦 𝘸𝘢𝘴 52.08%, 𝘢𝘯𝘥 𝘵𝘩𝘦 𝘷𝘪𝘨𝘰𝘳 𝘪𝘯𝘥𝘦𝘹 𝘸𝘢𝘴 40.20%. 𝘛𝘩𝘦 𝘳𝘦𝘴𝘶𝘭𝘵𝘴 𝘰𝘧 𝘵𝘩𝘦 𝘢𝘯𝘢𝘭𝘺𝘴𝘪𝘴 𝘰𝘧 𝘱𝘩𝘺𝘴𝘪𝘰𝘭𝘰𝘨𝘪𝘤𝘢𝘭 𝘲𝘶𝘢𝘭𝘪𝘵𝘺 𝘢𝘯𝘥 𝘱𝘩𝘺𝘴𝘪𝘤𝘢𝘭 𝘲𝘶𝘢𝘭𝘪𝘵𝘺 𝘴𝘩𝘰𝘸𝘦𝘥 𝘵𝘩𝘢𝘵 𝘥𝘳𝘺𝘪𝘯𝘨 𝘵𝘪𝘮𝘦 𝘰𝘧 24.14 𝘩𝘰𝘶𝘳𝘴 𝘢𝘯𝘥 𝘥𝘳𝘺𝘪𝘯𝘨 𝘵𝘦𝘮𝘱𝘦𝘳𝘢𝘵𝘶𝘳𝘦 𝘰𝘧 52.62 °𝘊 𝘸𝘦𝘳𝘦 𝘵𝘩𝘦 𝘰𝘱𝘵𝘪𝘮𝘶𝘮 𝘵𝘳𝘦𝘢𝘵𝘮𝘦𝘯𝘵𝘴 𝘧𝘰𝘳 𝘤𝘰𝘳𝘯 𝘴𝘦𝘦𝘥 𝘥𝘳𝘺𝘪𝘯𝘨.